Origin of the allotriploid "híbrido de timor" through a karyotype comparison with its coffea ancestors - Oliveira, Stéfanie Cristina de (2017)
Among the Coffea, there is a natural hybrid denominated “Híbrido de Timor” (HT), found on Timor Island in 1927. HT 'CIFC 4106', which represents the first HT plant, possesses 2n = 3x = 33 chromosomes and 1C DNA value equal 1C = 2.10 pg. Chromosomal number, nuclear 1C DNA content and geographical evidences support a possible allotriploid origin from fusion of a reduced reproductive cell of Coffea arabica (2n = 4x = 44) and Coffea canephora (2n = 2x = 22). C. arabica, another allopolyploid, accumulates studies that seek to unravel its progenitors. Molecular and karyotype data suggests that this true allotetraploid was formed from a reduced reproductive cell of C. canephora (CC) and another C. eugenioides (EE) followed by a polyploidization event. In this way, C. arabica genome is represented as C aC a E a E a . Based on this evidences, we formulate the following hypothesis: HT ‘CIFC 4106’ genome is CCa E a ? The present study aimed to cytogenetically characterize C. eugenioides, C. canephora, C. arabica and HT 'CIFC 4106'. The combination of morphometric data, flow and image cytometries and 5S rDNA fluorescente in situ hybridization (FISH) expanded knowledge about the evolutive origin and genome structure of HT ‘CIFC 4106’. HT 'CIFC 4106' karyogram evidenced chromosomes group delimited according to the class and DNA value similar. Based on these karyotype features was possible show the presence of two identical genomes in HT 'CIFC 4106', possibly of C. canephora (CC) and a distinct genome (C. eugenioides, E). HT 'CIFC 4106' chromosomes presented class, DNA content identical to the chromosomes of C. eugenioides, C. canephora and C. arabica. 5S rDNA sites were detected in two HT ‘CIFC 4106’ chromosomes. Distribution patterns of 5S markings found in C. eugenioides and C. canephora revealed in this study corroborate with HT ‘CIFC 4106’ CCa E a genome hypothesis. The 15 distribution of the 5S rDNA sites found in three Coffea allied to the chromosomal DNA content and class shows chromosomes similar to C. eugenioides and C. canephora in HT ‘CIFC 4106’. In addition, the data reveal possible structural chromosomal rearrangements along the evolution of HT ‘CIFC 4106’